Kecenderungan orthorexia nervosa pada mahasiswa program studi gizi - Khusna, Syifaul; Warsini, Sri; Helmiyanti, Siti (Jurnal Gizi Klinik Indonesia, 2023)
Orthorexia nervosa tendency in nutritional studentsBackground: Orthorexia nervosa (ON) is a condition when someone is over obsessive about healthy food, and focus on food quality can lead to disturbed life. One of the vulnerable group is health related student which include health nutrition student. There is no research about this.Objectives: The study aims to  evaluate the prevalence of ON tendency on nutritional student, and explore and investigate the related factors between common characteristics and ON tendency.Methods: This study is descriptive research with a cross-sectional design involving 100 samples of nutrition students chosen by proportional random sampling. Questionnaire-based on an Indonesian version of ORTO-15 which has been validated. Data were analyzed using Mann-Whitney, Spearman Rank, and multivariate.Results: Orthorexia nervosa tendency was documented in 38% of the sample (using cut-off point 40). The mean score of the participants from the ORTO-15 test is 39.99± 3.221. Meal frequencies were associated with ON tendency (p=0.040). While no significant correlation between orthorexic tendencies with sex, allergy, dietary pattern, frequent exercising, amount of social media accounts, and accessing social media duration (p>0.05).Conclusions: The prevalence of ON tendencies in nutritional students is 38%. The factor that influences the tendency to ON is the frequency of eating.